The myth of the ping-pong diplomacy in the light of future attempts to use sport to create international convergence - Kobierecki, Michał Marcin (Myths and Stereotypes in the Collective Representations, 2019)
The aim of the article is to investigate the ways of using sport in order to shape international brand of a state. Accordingly, various forms of shaping state’s international image with the use of sports diplomacy have been analyzed and shortly described – within the proposed typology. An attempt to verify a hypothesis concerning sports diplomacy as a significant tool of shaping state’s international brand was also made. Badanie zostało sfinansowane przez Narodowe Centrum Nauki w ramach projektu nr 2015/19/D/HS5/00513.